Antibacterial Potential of Endemic Medicinal Plants of the Maluku Islands, Indonesia, against Urinary Tract Infection Pathogens - Eka Astuty; Vinsa Delia Luhulima; Stefanus Cahyo Ariwicaksono (Folia Medica Indonesiana)
Highlights: 1. Clove, cinnamon, and eucalyptus have found to be able to providing antibacterial agents for urinary tract infection (UTI). 2. Ethanol extracts derived from clove leaves, cinnamon bark, and eucalyptus leaves can inhibit pathogenic bacteria responsible for UTI, indicating their potential as sources of bioactive compounds for UTI medication development.